Alberta [South] - Canada. Department of Mines and Technical Surveys (Department of Mines and Technical Surveys Canada, 1962)
This is a map of Alberta in 1962 showing settlements, First Nations reserves, Metis colonies, provincial and national parks, forest reserves, irrigation canals, railways, cities and towns. It consists of 2 parts - South and North (see also Alberta [North]). Scale 1:760,320, or 12 miles to 1 inch. Relief shown by spot heights. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ . Shows settlements, First Nations reserves, Metis colonies, provincial and national parks, forest reserves, irrigation canals, railways, cities and towns.